Synthesis of thiazoloquinolinone derivatives: molecular docking, MD simulation, and pharmacological evaluation as VEGFR-2 inhibitors - Zeinab Amiri; Mohammad Bayat; Davood Gheidari (BMC Chemistry)
Abstract We synthesized a series of novel thiazoloquinolinone derivatives, achieving moderate to high yields ranging from 74 to 96%, and assessed their efficacy against Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) using in silico methodologies. The structures of these compounds were characterized through various spectroscopic techniques, including 1H-NMR, 13C-NMR, IR, and mass spectrometry. Comprehensive computational analyses, encompassing molecular docking, molecular dynamics (MD) simulations, and absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling, were conducted. Docking studies with VEGFR-2 revealed that all synthesized compounds exhibited docking scores between − 3.24 and − 6.63, indicating varying degrees of binding affinity. Notably, compound (5e) demonstrated the strongest binding affinity with an energy of − 6.63 kcal/mol. The MD simulations indicated that Lys868 was one of the amino acids exhibiting the highest frequency of interaction throughout the simulation. Analysis of the ADMET and physicochemical properties revealed that all inhibitor compounds possess favorable pharmacological characteristics.